The Prognostic Nutritional Index before durvalumab after chemoradiation predict the overall survival in patients with stage III non-small cell lung cancer. (12th December 2023) - Matsuura, Shun; Serizawa, Sayaka; Yamashita, Ryoma; Morikawa, Keisuke; Ito, Yutaro; Hiramatsu, Toshiya; Mochizuki, Eisuke; Tanaka, Kazuki; Akiyama, Norimichi; Tsukui, Masaru; Koshimizu, Naoki; Kosugi, Takashi
Abstract: Background: Adjuvant durvalumab after chemoradiation has become the standard of care for patients with stage III NSCLC, according to the PACIFIC trial. Whether biomarkers before durvalumab for patients with stage III NSCLC showed predictive and prognostic effects remains unknown. Methods: This is a retrospective study in the Fujieda Municipal General Hospital between October 2018 and March 2022. We assessed the predictive value of the Prognostic Nutritional Index (PNI) in stage III non-small cell lung cancer (NSCLC) patients treated with durvalumab after chemoradiation. Results: After applying the inclusion and exclusion criteria, the study included 56 patients for further analysis. The median follow-up period was 17.6 months (range, 3.0–45.4 months). According to receiver operating characteristic curve results, the PNI cutoff value to predict overall survival (OS) was 37.9, with sensitivity and specificity at 67.9% and 67.9%. Accordingly, the patients were divided into low- and high-PNI groups. Patients with the low-PNI group had a significantly shorter progression-free survival compared to the high-PNI group (median, 9.1 vs. 21.3 months, p  = 0.032). OS was also shorter in the low-PNI group (median, 19.0 months vs. not reached, p  < 0.001). In the multivariate Cox hazards regression analyses, the high-PNI was an independent prognostic factor for OS (hazard ratio, 0.187; 95% confidence interval, 0.046–0.760; p  = 0.019). Conclusions : It seems that PNI could be used as a predictor for OS in patients with stage III NSCLC treated with durvalumab after chemoradiation. KEY MESSAGES: Inadequate immunocompetence and nutritional status after chemoradiation therapy may result in poor antitumor efficacy of ICIs. Pretreatment immune and nutritional assessment using PNI could be considered an independent predictor for the survival of stage III NSCLC patients treated with durvalumab after chemoradiation therapy.